Effect of Joint forest Management Practices on Nutrient Status of Soil - a Case Study - Gupta, H. S. (Indian Forester, 2007)
An experiment conducted in selected village forests of Ranchi and Hazaribagh districts (both where JFM is practiced and where not practiced), indicates that forest where JFM is practiced has better soil characteristics. Though this experiment is not a perfect one and it has to explain some questions but it has definitely given a hint that JFM has certainly positive effect on soil nutrient status of the forest.